Network modelling approaches for calculating wholesale NGA prices: A full comparison based on the Greek fixed broadband market - Nikos Ioannou; Vangelis Logothetis; Konstantin Petre; Markos Tselekounis; Aris Chipouras; Dimitris Katsianis; Dimitris Varoutas (International Telecommunications Society (ITS), 2020)
According to the 2013/466/ΕC Recommendation for setting copper and NGA wholesale access prices where cost orientation is imposed as a remedy, NRAs should adopt a BU LRIC+ costing methodology that estimates the current cost that a hypothetical efficient operator would incur to build a modern efficient NGA network. The starting point of modeling an efficient operator investing in NGA networks is the network modeling approach. In this paper, we compare the most widely adopted network modeling approaches in terms of wholesale FTTH prices. In particular, the modified scorched node approach is compared to the extreme cases of the scorched node and the scorched earth approaches. Τhe comparison between the aforementioned scenarios sheds light on the impact of each approach on the wholesale FTTH prices. The main finding of this paper is that the scorched earth approach leads to a maximum of 10% reduction in the short-term access prices compared to the most inefficient scorched node approach, whereas further extending its optimizations by optimizing the number of central offices, both the short-term and long-term wholesale price reductions are quite significant (more than 20%) regardless of service speeds. Obviously, these findings provide valuable information to both network operators and telecom regulators.
Keywords: L43; L51; L96; 330; FTTH; (Modified) scorched node; scorched earth; wholesale NGA prices